2012
DOI: 10.1016/j.juro.2012.04.100
|View full text |Cite
|
Sign up to set email alerts
|

Altered Caveolar Mediated Purinergic Signaling in Spontaneously Hypertensive Rats with Detrusor Overactivity

Abstract: Caveolar depletion in WKY bladders results in a functional phenotype analogous to that of overactive SHR bladder. The intrinsically decreased caveolae in SHR rats causes loss of the caveolar mediated regulation of purinergic signaling and augmented spontaneous activity, conditions that may lead to detrusor overactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…To precisely quantify the co-expression of endothelial and mesenchymal markers, the Duolink In Situ assay (Olink Bioscience, Uppsala, Sweden) was applied [ 17 19 ]. The frozen sections were incubated overnight at 4°C with a mixture of primary antibodies, including anti-human CD31 antibody (mouse, 1:20; catalog code: NB600-562) and FSP-1 (rabbit, 1:100; Abcam, Cambridge, UK; catalog code: ab27957), after incubation with blocking buffer solution (Dako, Protein Block Serum-Free).…”
Section: Methodsmentioning
confidence: 99%
“…To precisely quantify the co-expression of endothelial and mesenchymal markers, the Duolink In Situ assay (Olink Bioscience, Uppsala, Sweden) was applied [ 17 19 ]. The frozen sections were incubated overnight at 4°C with a mixture of primary antibodies, including anti-human CD31 antibody (mouse, 1:20; catalog code: NB600-562) and FSP-1 (rabbit, 1:100; Abcam, Cambridge, UK; catalog code: ab27957), after incubation with blocking buffer solution (Dako, Protein Block Serum-Free).…”
Section: Methodsmentioning
confidence: 99%
“…Research has shown that a large variety of receptors can be expressed in, or translocated to, these structures; thus the caveolae mediated signal transduction may be important for bladder contraction (Li et al, 1995;Lisanti et al, 1994;Shaul & Anderson, 1998). Furthermore, the caveolae have been shown to be involved in urinary bladder disorders such as overactive bladder, bladder hypertrophy and bladder cancer (Cohen et al, 2004;Cristofaro et al, 2012;Fu et al, 2017). A study from 2012 showed a decrease of the caveolae specific protein caveolin-1 in cyclophosphamide-induced (CYP-induced) cystitis (Kim et al, 2012).…”
Section: Caveolaementioning
confidence: 99%
“…Caveolae have also been accredited other functional roles such as endocytosis (Parton & Simons, 2007). During pathological bladder conditions such as detrusor overactivity, the caveolaemediated signalling appears to be altered due to a change in caveolae density (Cristofaro et al, 2012). In this thesis, the plausible involvement of caveolaedependent signalling for the ATP-evoked release of acetylcholine was examined.…”
Section: Functional Roles Of Caveolae In Urinary Bladder Signallingmentioning
confidence: 99%
“…Polyak ’s research has shown that the decreased number of caveolae and caveolin protein expression in hypertrophied bladders may contribute to alterations in signal transduction pathways 29 , whereas Shakirova provided new evidence that rat detrusor hypertrophy due to outflow obstruction led to an increased density of membrane caveolae to promote contraction in response to bradykinin 30 . The decreased caveolae were associated with impaired purinergic signaling in the detrusor 31 . In our transmission electron microscopy experiment, we also found that the density of caveolae and the expression of three structural proteins were down-regulated in the ICCs-DM of diabetic bladders.…”
Section: Discussionmentioning
confidence: 96%